Factors influencing investors to invest in Amanah Mutual Berhad funds / Nur Fadhlina Mohd. Shairi (Faculty of Business Management, 2008)
As we know, to identify factors that influencing investors to invest is very important to any unit trust company. In this research, the study is made towards factors influencing investors to invest in AMB funds in Klang Valley. For the purpose of the study, descriptive and causal research was employed in order to identify which factors most influencing investors to invest in AMB funds. Convenience sampling has been utilized with 95 respondents or the sample size. The close ended questionnaire was used as the survey instrument. By using the analysis generated by SPSS (Statistical Package for the Social Science), results are analyzed and deduction being drawn. Looking at the result in data analysis, cross tabulation, correlation, hypothesis testing and regression. Finally, the finding from this study concludes that factors most influencing investors to invest in AMB funds are sales force and financial performance.